Verification of Matthaeus Praetorius’ Mythical Material on Oak - Vičinskas, Žydrūnas (Tautosakos darbai, 2016)
The authenticity of Matthaeus Praetorius’ (Matthäus Prätorius) mythical information on Perdoytus, Wejopattis, Gardouten, Bangpjtjs, Luobgelda (partly Bardoayts) in the context of the 16th–17th centuries was already in the focus of some previous publications. The performed research revealed certain tendency of information noise manifesting in transmission of inaccurate data / ideas / thoughts – information X – to another person; therefore, it makes sense to continue analyzing the reliability of the mythical material by Praetorius. The article aims at verifying the reliability of the mythical information about the oak provided in the work by Praetorius, as well as reviewing and evaluating the interpretations on the oak by the well-known researchers of the 20th–21st centuries, who have analyzed the selected data of Praetorius. According to the results of the analysis, the aim of the articles is also highlighting the main features of the individual authors’ interpretative system. As revealed by the analysis of interpretations of Praetorius’ mythical material, the researchers of the 20th–21st centuries used and viewed Praetorius’ information in two ways. They either (1) did not consider the issue of authenticity of the Praetorius’ mythical data on oak, regarding it as sufficiently reliable and suitable to use in their scientific publications (Petras Klimas, Jonas Bertulaitis, Aukusti Robert Niemi, Marija Gimbutienė, Pranė Dundulienė, Nijolė Laurinkienė, Elvyra Usačiovaitė); or (2) understood the problem of verification of the material and tried solving it to some extent (Zenonas Slaviūnas, Gintaras Beresnevičius, Dainius Elertas). Before assessing the authenticity of Praetorius’ mythical material on oak, it must be said that most of the information provided in the first chapter of the fourth book of the work are inauthentic rewrites, but the sixth and twenty-sixth subchapters and the twenty-fourth subchapter of the fifth chapter are considered to be authentic mythical data. As for the reliability of sketches, the sketch of Romava ąžuolas (‘Romava Oak’) as well as the painting of Ąžuolas Ragainės lauke (‘The Oak on the Ragainė Field’) are considered partially authentic. Regarding the features of the Praetorius’ interpretative system, it may be said that: 1) written sources are used; 2) they are viewed in three ways: positively / negatively / ambiguously; 3) mythical data is interpreted linguistically; 4) assumptions are constructed using information from the chronicles and material from the contemporaries; 5) sketches of mythologemes are made.
Keywords: -